Isolation and characterization of cellulose from wastepaper and corn cob - Shahida Norikmal, Binti Samsudin (Universiti Malaysia Sarawak (UNIMAS), 2009)
The focus of this study is to isolate cellulose from both cellulosic materials obtained from wastepaper and corn cob by the isolation method and the dissolution of sample in the NaOH / thiourea / urea (NTU) solvent system. The cost effectiveness of the dissolution method was also investigated. The cellulose obtained from wastepaper and corn cobs were characterized by FTIR spectrometer, Scanning Electron Microscopy (SEM), and the CHN Elemental Analyzer. The best method for cellulose isolation was the isolation method that involved reflux with 50 mL of 20% (v/v) mixture of nitric acid (HNO3) in ethanol for 7 hours with a cellulose yield of 52.9% and 78.6 % for corn cob and wastepaper, respectively.